Gauging Indoor Air Quality with Inexpensive Gas Sensing Technologies. (2016) - Perez, Alvaro Ortiz; Bierer, Benedikt; Eaksen, Ponkanok; Wöllenstein, Jürgen; Palzer, Stefan
Abstract: Here we present a sensor system that is capable of detecting trace gases related to indoor air quality and well-being inside. Using a combination of optical and solid-state technologies we aim at detecting the key pollutants in the indoor environment. The sensing system is equipped with wireless technology such that the data obtained may be transmitted and made available to cloud-based applications. The information may then be used to understanding the exposures of individuals to these pollutants, characterizing the levels that trigger health effects, and balancing the risk from air pollutants with the benefits of improved energy management and insulation.